2017
DOI: 10.1084/jem.20160801
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 on tumor cells is sufficient for immune evasion in immunogenic tumors and inhibits CD8 T cell cytotoxicity

Abstract: Both tumor- and host-derived PD-L1 can play critical roles in immunosuppression; differences in tumor immunogenicity appear to underlie their relative contributions. Juneja et al. show that in immunogenic MC38 tumors, PD-L1 on tumor cells dominates in suppressing tumor immunity by inhibiting CD8 T cell cytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
525
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 676 publications
(560 citation statements)
references
References 37 publications
33
525
1
1
Order By: Relevance
“…This phenomenon is associated with enhanced T cell activation in PD-L1 -/-and PD-1 -/-mice as compared with WT mice. In addition, differential tumor cell numbers and tumor immunogenicity may potentially be involved in determining different levels of tumor outcomes in the MC38-bearing mouse model (30,31). Thus far, clinical studies with the PD-L1 and PD-1 blockade have not rigorously examined or specifically quantified PD-L1 expression on APC subsets versus tumor cells in TDLNs and tumor tissues in cancer patients (2).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is associated with enhanced T cell activation in PD-L1 -/-and PD-1 -/-mice as compared with WT mice. In addition, differential tumor cell numbers and tumor immunogenicity may potentially be involved in determining different levels of tumor outcomes in the MC38-bearing mouse model (30,31). Thus far, clinical studies with the PD-L1 and PD-1 blockade have not rigorously examined or specifically quantified PD-L1 expression on APC subsets versus tumor cells in TDLNs and tumor tissues in cancer patients (2).…”
Section: Discussionmentioning
confidence: 99%
“…The results from the present study, with immune cell-specific PD-L1 expression being an independent prognostic factor while its expression in tumour cells was not, are coherent with previous research 16 , 23-26 and demonstrate that PD-L1 expression in immune cells and tumour cells might carry different prognostic values and might be regulated by distinct mechanisms. Furthermore, although tumour cell-specific PD-L1 expression has been validated as a predictive marker for response to PD-1 or PD-L1 blockade in several cancers, 11 , 38 , 39 recent studies now suggest that PD-L1 expression in tumour-infiltrating myeloid and T cells also play a critical role in immunosuppression, 38 , 40-43 and should possibly be taken into account in assessment scoring for PD-1/PD-L1 blockade.…”
Section: Discussionmentioning
confidence: 99%
“…However, the essential or sufficient role of PD-L1 on tumor versus nontumor cells for immune evasion is still unclear (1,22,23). Recently, the importance of PD-L1 on tumor versus host cells during tumor growth has been intensively debated (24)(25)(26)(27). In one study, the role of PD-L1 during tumor formation was studied (25).…”
Section: Pd-l1 In Host Apcs Is Essential For the Responses To Pd-l1 Bmentioning
confidence: 99%
“…It is suggested that both hostand tumor-PD-L1 contribute to immune suppression during the establishment of tumors (25). In contrast, another study shows that PD-L1 in tumor cells is sufficient for immune evasion (26). In the latter study, a lower cell number was used to slow tumor growth and induce a more robust adaptive immune response.…”
Section: Pd-l1 In Host Apcs Is Essential For the Responses To Pd-l1 Bmentioning
confidence: 99%
See 1 more Smart Citation